METABOLISM OF SULFATE BY THE CHROMATOPHORE OF RHODOSPIRILLUM - Ibanez, M. L. (1962)
Ibanez, M. L. (The Pennsylvania State University, University Park) and E. S. Lindstrom. Metabolism of sulfate by the chromatophore of Rhodospirillum. J. Bacteriol. 84:451–455. 1962.—The chromatophore of Rhodospirillum rubrum was shown to possess enzymes for the activation and reduction of inorganic sulfate. The chromatophore was able to synthesize 3′-phosphoadenosine 5′-phosphosulfate (PAPS), using either exogenous adenosine triphosphate (ATP) or ATP synthesized via photophosphorylation. Light was required for the reduction of sulfate to a volatile form, presumably sulfite. Light enhanced the incorporation of sulfate-sulfur into cystine, cysteine, and cysteic acid of the chromatophore. This incorporation was probably the result of exchange reactions of reduced sulfur, not the result of net synthesis. The 100:1 ratio of the activation to reduction of sulfate and the inhibition of the reduction by exogenous ATP suggested that PAPS might not be the substrate for chromatophoral sulfate reduction.